MACROECONOMIC PERFORMANCE IN BRAZIL UNDER THE INFLATION TARGETING REGIME - Araujo, Elisangela; Araújo, Eliane; Ferrari Filho, Fernando (Investigación Económica, 2018)
ABSTRACT This study analyses theoretically and empirically the relationship between monetary institutions and macroeconomic performance in Brazil, in the period after the adoption of the inflation targeting regime (ITR), in 1999. The hypothesis is that the monetary institutions inhibited economic growth, rather than being effective at controlling inflation, whose main causes are related to structural and institutional factors, indexation process and domestic and external shocks. The main results of the ITR, embodied in the highly restrictive monetary policy, are the following negative effects: A reduction in Gross Domestic Product (GDP) growth rates, a rise in the stock of public debt and an appreciation of the domestic currency. Likewise, the itr has not been successful in maintaining inflation rate below its target. In this respect, revisions in the Brazilian monetary institutions would be essential to improve the results of the ITR, both in terms of actual inflation and economic performance. DESEMPEÑO MACROECONÓMICO EN BRASIL DESPUÉS DEL RÉGIMEN DE METAS DE INFLACIÓN RESUMEN Este estudio analiza teórica y empíricamente la relación entre las instituciones monetarias y el desempeño macroeconómico en Brasil en el periodo posterior a la adopción del régimen de metas de inflación (RMI) en 1999. La hipótesis es que las instituciones monetarias impidieron el crecimiento económico, más que controlar efectivamente la inflación, cuyas causas principales están relacionadas con factores estructurales e institucionales, procesos de indexación y choques internos y externos. Los principales resultados del RMI, consustanciados en la política monetaria altamente restrictiva, son los siguientes efectos negativos: una reducción de las tasas de crecimiento del producto interno bruto (PIB), un aumento del stock de deuda pública y una apreciación de la moneda nacional. Asimismo, el RMI no logró mantener la tasa de inflación por debajo de su meta. A este respecto, revisiones en las instituciones monetarias brasileñas serían esenciales para mejorar los resultados del rmi, tanto en términos de inflación como de desempeño económico.